Analysis of the Learning Process During Covid-19 Pandemic - Sri Rahayu; Tanto Hariyanto; Lisa Wulandari; Hirdayanti Finisia (Humanistic Network for Science and Technology (HNST), 2020)
After Covid-19 was declared as Pandemic by the WHO, all activities are lingered over barriers including teaching and learning activities. Learning methods are transformed into online learning to minimize the spread of Covid-19 virus. But in its implementation there are obstacles and shortcomings so that the learning process is disrupted. This research aimed to analyze the online learning process during the Covid-19 pandemic in Poltekkes Kemenkes Malang. Research method used in this study was qualitative description and used total sampling method in collecting respondent. The results showed that online learning was still not maximal at its implementation. The result analysis used Respondent Achievement Level (RAL). On the topic of learning process and learning atmosphere was at vulnerable 55% - 69% with the category